Pedoman Penyelenggaraan Kursus Pra Nikah Dalam Membentuk Keluarga Sejahtera - Osman, Osman; Saleh, Ahmad; Mas'udi, Mas'udi (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The aim of the research is to analyze and describe the legal basis for the publication of the Pre-Marriage Course Guidelines and its impact on forming a prosperous family. Research with a normative legal approach through the Legislative Approach and Case Approach. The research results show: Pre-Marriage Course Guidelines often give rise to varying interpretations, especially regarding obligations or policies regarding certificates obtained after taking the course. Some people believe that this certificate is not a requirement for complete marriage documents, especially after the issuance of new regulations which do not explicitly replace the previous regulations which required a Pre-Marriage Course certificate as part of the marriage documents. The government realizes that achieving success in achieving the objectives of the Pre-Marriage Course Guidelines requires active involvement from the community and community organizations.